The development of hybrid power transmission maintenance technology for Toyota car service station - Haddaji, Abdellatif (Харківський національний автомобільно-дорожній університет, 2023)
The object of study is the transmission of a hybrid car. The purpose of the work is to increase the efficiency of using a vehicle with a hybrid system by studying the advantages and disadvantages of various transmission schemes, as well as performing high-quality maintenance. Research methods - study and analysis of scientific and technical information, processing and systematization of technical data. The following tasks were set in the work: Perform an analysis of the development of hybrid cars using the example of the Toyota brand. Write a description of the most typical hybrid systems. Perform an analysis of the merits and demerits of each hybrid transmission scheme. Conduct an analysis of energy sources for a fuel cell hybrid electric vehicle. To study the design features of the Toyota Corolla hybrid system. Perform system description and identification. Set the location and description of the hybrid components. Perform hybrid transmission diagnostic tool analysis..
Keywords: hybrid; service; vehicle; transmission; types; options